Developmental motor problems and health-related quality of life in 5-year-old children born extremely preterm: A European cohort study
Aim To measure the association between cerebral palsy (CP) and non-CP-related movement difficulties and health-related quality of life (HRQoL) among 5-year-old children born extremely preterm (<28 weeks gestational age). Method We included 5-year-old children from a multi-country, population-based cohort of children born extremely preterm in 2011 to 2012 in 11 European countries (n = 1021). Children without CP were classified using the Movement Assessment Battery for Children, Second Edition as having significant movement difficulties (<= 5th centile of standardized norms) or being at risk of movement difficulties (6th-15th centile). Parents reported on a clinical CP diagnosis and HRQoL using the Pediatric Quality of Life Inventory. Associations were assessed using linear and quantile regressions. Results Compared to children without movement difficulties, children at risk of movement difficulties, with significant movement difficulties, and CP had lower adjusted HRQoL total scores (beta [95% confidence interval] = -5.0 [-7.7 to -2.3], -9.1 [-12.0 to -6.1], and - 26.1 [-31.0 to -21.2]). Quantile regression analyses showed similar decreases in HRQoL for all children with CP, whereas for children with non-CP-related movement difficulties, reductions in HRQoL were more pronounced at lower centiles. Interpretation CP and non-CP-related movement difficulties were associated with lower HRQoL, even for children with less severe difficulties. Heterogeneous associations for non-CP-related movement difficulties raise questions for research about mitigating and protective factors.